Characterization of Tunisian Castor Genotypes (Ricinus communis L.) Using RAPD Markers - Vivodík, Martin; Petrovičová, Lenka; Balážová, Želmíra; Gálová, Zdenka (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2018)
The aim of this work was to detect genetic variability among the set of 20 Tunisian castor genotypes using 5 RAPD markers. Amplification of genomic DNA of 20 genotypes, using RAPD analysis, yielded 42 fragments, with an average of 7.00 polymorphic fragments per primer. Number of amplified fragments ranged from 5 to 9, with the size of amplicons ranging from 200 to 1400 bp. The polymorphic information content (PIC) value ranged from 0.662 to 0.855 with an average of 0.780 and diversity index (DI) value ranged from 0.669 to 0.857 with an average of 0.785. The dendrogram based on hierarchical cluster analysis using UPGMA algorithm was prepared. Knowledge on the genetic diversity of castor can be used for future breeding programs for increased oil production to meet the ever increasing demand of castor oil for industrial uses as well as for biodiesel production.